THE EFFECT OF CHOLECALCIFEROL (VITAMIN D3) LEVELS ON VARIOUS TIMES AND DURATIONS OF EXPOSURE TO ULTRAVIOLET LIGHT (SUN EXSPOSURES) - Rachmad Bayu Kuncara; Roni Afriansya (Universitas Airlangga, 2023)
Sunbathing triggers the vitamin D production, which functions to increase the immune system. Vitamin D is very beneficial for the health of the body, exposure to sunlight in sufficient time the body will get adequate vitamin D. The purpose of this study is to explain the level of vitamin D3 levels that are often found to occur due to exposure to ultraviolet rays of the sun (Sun Exposures). This research method is an experimental study with a completely randomized design (CRD). The research design used was a randomized post test only control group design. Data were analyzed using the Kruskal Wallis test with statistical test results obtained levels of Cholecalciferol (Vitamin D3) with p value = 0.675 (> 0.05) meaning there was no difference in each treatment group.